ANALISIS PENGENDALIAN PIUTANG TERHADAP PENAGIHAN PIUTANG ARUS KAS PT.COWELL DEVELOPMENT TBK - Agustin Agustin (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2019)
This study aims to analyze the control of receivables on the collection of cash flowreceivables at PT.Cowell Development Tbk. The data analysis technique used inthis research is descriptive qualitative method. Qualitative descriptive analysis isa data analysis technique that is done by collecting data, clarifying data,explaining and analyzing so that it provides information and images that areappropriate to the problem being faced or researched. Sources of data in thestudy used are secondary data sources and primary data. From the results of thestudy show that the control of receivables is the billing process with a long time tothe bills that are due. PT. Cowell Development Tbk must be more active in thecollection of receivables so that the balance of the amount of receivables is nottoo large so that it will affect the effectiveness of cash flow.